Cough threshold in reflux oesophagitis: influence of acid and of laryngeal and oesophageal damage. Issue 6 (1st June 2000) - Benini, L; Ferrari, M; Sembenini, C; Olivieri, M; Micciolo, R; Zuccali, V; Bulighin, G M; Fiorino, F; Ederle, A; Cascio, V Lo; Vantini, I
Abstract : BACKGROUND: Gastro-oesophageal reflux is often associated with cough. Patients with reflux show an enhanced tussive response to bronchial irritants, even in the absence of respiratory symptoms. AIM: To investigate the effect of mucosal damage (either oesophageal or laryngeal) and of oesophageal acid flooding on cough threshold in reflux patients. PATIENTS: We studied 21 patients with reflux oesophagitis and digestive symptoms. Respiratory diseases, smoking, and use of drugs influencing cough were considered exclusion criteria. METHODS: Patients underwent pH monitoring, manometry, digestive endoscopy, laryngoscopy, and methacholine challenge. We evaluated the cough response to inhaled capsaicin (expressed as PD5, the dose producing five coughs) before therapy, after five days of omeprazole therapy, and when oesophageal and laryngeal damage had healed. RESULTS: In all patients spirometry and methacholine challenge were normal. Thirteen patients had posterior laryngitis and eight complained of coughing. Twenty patients showed an enhanced cough response (basal PD5 0.92 (0.47) nM; mean (SEM)) which improved after five and 60 days (2.87 (0.82) and 5.88 (0.85) nM; p<0.0001). The severity of oesophagitis did not influence PD5 variation. On the contrary, the response to treatment was significantly different in patients with and without laryngitis (p=0.038). In patients with no laryngitis, the cough threshold improved after five days with no further change thereafter. In patients with laryngitis, the cough threshold improved after five days and improved further after 60 days. Proximal and distal oesophageal acid exposure did not influence PD5. Heartburn disappeared during the first five days but the decrease in cough and throat clearing were slower. CONCLUSIONS: Patients with reflux oesophagitis have a decreased cough threshold. This is related to both laryngeal inflammation and acid flooding of the oesophagus but not to the severity of oesophagitis. Omeprazole improves not only respiratory and gastro-oesophageal symptoms but also the cough threshold.